Age of Trauma Onset and HPA Axis Dysregulation Among Trauma-Exposed Youth - Kuhlman, Kate Ryan (J Trauma Stress, 2015)
The hypothalamic–pituitary–adrenal axis (HPA axis) is a pathway through which childhood trauma may increase risk for negative health outcomes. The HPA axis is sensitive to stress throughout development; however, few studies have examined whether timing of exposure to childhood trauma is related to differences in later HPA axis functioning. Therefore, we examined the association between age of first trauma and HPA axis functioning among adolescents, and whether these associations varied by sex. Parents of 97 youth (aged 9–16 years) completed the Early Trauma Inventory (ETI), and youth completed the Socially-Evaluated Cold-Pressor Task (SECPT). We measured salivary cortisol response to the SECPT, the cortisol awakening response, and diurnal regulation at home across 2 consecutive weekdays. Exposure to trauma during infancy related to delayed cortisol recovery from peak responses to acute stress, d = 0.23 to 0.42. Timing of trauma exposure related to diverging patterns of diurnal cortisol regulation for males, d = 0.55, and females, d = 0.57. Therefore, the HPA axis may be susceptible to developing acute stress dysregulation when exposed to trauma during infancy, whereas the consequences within circadian cortisol regulation may occur in the context of later trauma exposure and vary by sex. Further investigations are warranted to characterize HPA axis sensitivity to exposure to childhood trauma across child development.